Using otolith weights to estimate age for eastern sea garfish, Hyporhamphus australis - Stewart, John; Broadhurst, Matt K.; Tolhurst, Daniel J. (Frontiers in Fish Science, 2024)
The most common method of estimating teleost ages is via sectioned otoliths. With diminishing funding and policies around cost-recovery from fishing industries, exploring cost-effective methods of estimating ages is warranted. The present study used 18 years of size-at-age data collected from monitoring of the commercial halfbeak (Hyporhamphus australis) fishery off New South Wales, Australia, to predict age classes from otolith weights, while considering other sources of variability such as sex, fish length, and year, month, and location of capture. We observed a significant linear relationship between age class and mean otolith weight. A generalized linear mixed model predicted 1-year olds with an 82% success rate; but was less successful for other ages. Year of sampling explained the greatest variability in the model and the distributions of otolith weights for each age class had considerable overlap. We conclude that substantial inter-annual variability in the age-class to otolith weight relationship, in addition to the relatively low precision when aging H. australis by counting annuli in sectioned otoliths, limits the predictive capacity of this model for future monitoring. Nevertheless, substantial cost savings could be made through recalibrating the model for new samples through direct aging of a subset of otoliths each year. The population of H. australis is continuing to rebuild from a previously overfished state, with an expectation that older fish will become more abundant in the fishery. Age estimation from counting annuli in sectioned otoliths is likely to be the most reliable method of identifying older individuals.